Adherence and barriers to hyperinsufflation in children with congenital muscular dystrophy. Issue 7 (22nd November 2016) - Pascoe, John E.; Sawnani, Hemant; Mayer, Oscar H.; McConnell, Keith; McDonough, Joseph M.; White, Cynthia; Rutkowski, Anne M.; Amin, Raouf S.; Modi, Avani C.
Summary: Background: Congenital muscular dystrophy (CMD) is a rare, inherited neuromuscular disease characterized by progressive muscle weakness, thoracic insufficiency, and ultimately respiratory failure. Adherence to respiratory therapies in children with neuromuscular disorders is unknown. This study examined the multimodal assessment of adherence and barriers to 15 min, twice daily hyperinsufflation in children with CMD. Adherence was hypothesized to be greater than 50% and discomfort, embarrassment, and difficulty finding time were hypothesized to be barriers. Methods: Participants included 18 children with CMD. Personalized hyperinsufflation settings were determined based on pressure–volume measurements at each study visit. Adherence was measured by a daily phone diary (DPD) and by electronic data download from the hyperinsufflation device. The DPD was conducted twice over a 48‐hr period to capture a weekend and weekday, with the goal being 60 min of hyperinsufflation over the 48 hr (100% adherence). The hyperinsufflation objective electronic data reflected daily use of hyperinsufflation for the same 48‐hr period. Data from DPD and the corresponding hyperinsufflation device data were used for analyses. Results: Adherence to hyperinsufflation was 40% via DPD and 44% for electronic data, with strong convergence between methods (r = 0.75, P < 0.001). Surprisingly, 53% of participants reported no barriers despite low adherence. Social distractions and family obligations were identified as barriers. There were no differences in adherence between those who did and did not endorse barriers to hyperinsufflation (DPD: t(13) = 0.44, P = n.s.; hyperinsufflation device: t(13) = −0.23, P = n.s.). Conclusion: Adherence to hyperinsufflation is a significant problem in children with CMD and families have difficulty identifying adherence barriers. An important next step is to encourage open dialog around adherence barriers and promote adherence behaviors via intervention.Pediatr Pulmonol. 2017; 52:939–945. © 2016 Wiley Periodicals, Inc